The effect of using swamp water for daily needs on the saliva pH of non-smoking male farmers in Senajam Village, West Kalimantan Province: Pengaruh penggunaan air rawa sebagai kebutuhan keseharian terhadap pH saliva petani laki-laki non perokok di Dusun Senajam Provinsi Kalimantan Barat - Ganesha, Raziv; Dermawan, I Gusti Ngurah Putra; Dewi, Intan Kemala; Dayuta, Agustina Ursula (Makassar Dental Journal, 2025)
With a balanced pH, saliva protects the surface of the teeth from damage, inhibits the growth of pathogenic bacteria, and sup-ports the natural remineralisation process in tooth enamel. The quality of water used on a daily basis plays an important role in overall health, including dental and oral health. Different types of water have unique characteristics, including pH or acidity le-vels, which can affect oral health and surrounding tissues. Based on this background, this study aims to provide further insight into the pH condition of saliva in non-smokers, particularly in the male farming community in Senajam Hamlet who use swamp water for their daily needs, thereby revealing the effect of the habit of using swamp water, which has an acidic concentra-tion, on oral health. The results showed that 58% of the study participants had acidic values, 10.5% had alkaline values, and 31.5% had normal values. It was concluded that long-term use of acidic swamp water contributes to a decrease in saliva pH.